2006
DOI: 10.1590/s0100-67622006000600007
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de raizes e da parte aérea de clones de híbridos de Eucalyptus grandis x Eucalyptus urophylla e de Eucalyptus camaldulensis x Eucalyptus spp submetidos a dois regimes de irrigação no campo

Abstract: RESUMO -O presente estudo objetivou subsidiar a seleção de genótipos de eucalipto para plantio em ambientes com disponibilidade variável de água no solo, através da análise do crescimento de raízes na fase inicial de estabelecimento da planta no campo e de sua associação com o crescimento das plantas adultas. Foram utilizados os clones 0063, 0321, 1250, 1260 e 1277 de eucalipto, sob dois regimes de irrigação, a partir de seis meses de idade, em condições de campo, no norte do Estado da Bahia. O experimento foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 8 publications
2
21
0
20
Order By: Relevance
“…In contrast, the lowest values (0.1118), lower by approximately 70%, was obtained under optimal water supply conditions (100% ETpc) in the lowest salinity level (1.72 dS m -1 ). These results support the inferences of Reis et al (2006), who reported that the root shoot -1 ratio may increase with increasing water stress, given that it is expected that plants have more developed root system when grown under severe water deficits. Thus, according to the estimated mathematical model, the water favoring represented by the increment in ETpc tends to reduce the of the root dry biomass shoot -1 ratio value (Table 4; Figure 1e).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, the lowest values (0.1118), lower by approximately 70%, was obtained under optimal water supply conditions (100% ETpc) in the lowest salinity level (1.72 dS m -1 ). These results support the inferences of Reis et al (2006), who reported that the root shoot -1 ratio may increase with increasing water stress, given that it is expected that plants have more developed root system when grown under severe water deficits. Thus, according to the estimated mathematical model, the water favoring represented by the increment in ETpc tends to reduce the of the root dry biomass shoot -1 ratio value (Table 4; Figure 1e).…”
Section: Resultssupporting
confidence: 91%
“…Clonal propagation has allowed the adoption of hybridization in breeding programs for commercial exploitation of the heterosis in Eucalyptus genus. The technique is commonly applied to identify eucalypts hybrids with increased stress tolerance [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the evaluated parameters are strongly linked to a genetic character. REIS et al (2006), the Grancam hybrid tended to higher height, diameter and volume in the non-irrigated system, different behavior in relation to Urograndis hybrid, whose growth has tended to be higher in the irrigated treatment. However, these same authors explained their higher growth under water stress, the fact that the Grancam hybrid has depth root (0.97 m) and the highest proportion of biomass allocated to the root system (25.94%).…”
Section: Resultsmentioning
confidence: 80%
“…Where: θ fc -soil moisture at field capacity (matric potential of -10 kPa, m 3 m -3 ); θ pwp -soil moisture in the permanent wilting point (matric potential of -1500 kPa m 3 m -3 ); Z -depth of the root system, 970 mm (REIS et al, 2006); "p" -factor of soil water depletion for conifers (0.7) as recommended by ALLEN et al (1998). (4) The EAW Loc was 38.9 and 58.8 mm for dripping and micro sprinklers.…”
Section: (Eucalyptus Grandis X Eucalyptus Camaldulensis)mentioning
confidence: 99%